ASSESSMENT OF LEVELS OF PHYSICAL ACTIVITY IN PERIMENOPAUSAL WOMEN - N Rashmi, Ronghe; Neha, Gotmare A (International Journal of Clinical and Biomedical Research, 2017)
Aim: Various physical, psychological and hormonal changes during the perimenopause may affect their quality of life. It results in Joint pain, stiffness and urinary incontinence may limit the ability to take the exercise and to socialize. Poor sleep and mood changes can have an impact on women`s ability to work effectively. Objective: To categories level of physical activity in terms of light, moderate and vigorous through RAPA scale. Methodology: Questionnaire based survey was carried out in 100 perimenopausal women aged 45 to 55 years. After the anthropometric and demographic assessment RAPA was administered and then data was analyzed. Result: Out of 100 subjects only 17 women were categorized as active with moderate physical activity for 30 minutes on 5 or more days of week and 10 did vigorous physical activity for 20 minutes for 3 or more days a week and were called as active. Out of the 10 active only 4 did flexibility and no strengthening. Conclusion: Only 10 perimenopausal women could reach second level of RAPA. 22 were eliminated in question no. 1 i.e. they were inactive apart from daily household activities . KEY WORDS: Perimenopausal women; Rapid Assessment of Physical Activity.